2017
DOI: 10.3748/wjg.v23.i11.2068
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after total vs distal gastrectomy with Roux-en-Y reconstruction: Use of the Postgastrectomy Syndrome Assessment Scale-45

Abstract: AIMTo investigate the detrimental impact of loss of reservoir capacity by comparing total gastrectomy (TGRY) and distal gastrectomy with the same Roux-en-Y (DGRY) reconstruction. The study was conducted using an integrated questionnaire, the Postgastrectomy Syndrome Assessment Scale (PGSAS)-45, recently developed by the Japan Postgastrectomy Syndrome Working Party.METHODSThe PGSAS-45 comprises 8 items from the Short Form-8, 15 from the Gastrointestinal Symptom Rating Scale, and 22 newly selected items. Uni- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
1
28
0
2
Order By: Relevance
“…Recent studies have reported that distal gastrectomy results in a better long‐term survival for patients with distal gastric cancer compared with total gastrectomy . Also, patients who undergo total gastrectomy have a reduced postoperative quality of life when compared with patients who undergo distal gastrectomy . Adenocarcinoma of the esophagogastric junction (AEG) is a type of malignant tumor located between the esophagus and stomach and was initially characterized in 1999 by Siewert .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that distal gastrectomy results in a better long‐term survival for patients with distal gastric cancer compared with total gastrectomy . Also, patients who undergo total gastrectomy have a reduced postoperative quality of life when compared with patients who undergo distal gastrectomy . Adenocarcinoma of the esophagogastric junction (AEG) is a type of malignant tumor located between the esophagus and stomach and was initially characterized in 1999 by Siewert .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Also, patients who undergo total gastrectomy have a reduced postoperative quality of life when compared with patients who undergo distal gastrectomy. 3 Adenocarcinoma of the esophagogastric junction (AEG) is a type of malignant tumor located between the esophagus and stomach and was initially characterized in 1999 by Siewert. 4 AEG was known to have unique clinicopathological characteristics and biological behavior.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized, however, that the reconstruction procedure could still influence the QOL and nutritional outcomes in the long term [12]. Moreover, Postgastrectomy Syndrome Assessment Scale (PGSAS) [13], new integrated questionnaires to more specifically address the issue of QOL after gastrectomy, have recently emerged and shown promise in several observational studies [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[21] и М. Takahashi и соавт. [22] подтверждают более тяжелый и длительный период восстановления физической и социальной активности после тотальной радикальной операции, по большей части в плане расстройства питания вследствие полного отсутствия желудка и лимитирования количества поступающей пищи. По данным М. Takahashi и соавт.…”
Section: How To Decide Surgical Procedures Fro Esophagogastric Junctiounclassified
“…По данным М. Takahashi и соавт. [22], потеря в весе после операций на протяжении первого года составила 13,8% в группе тотальной гастрэктомии, 8,9% -в группе пар-ОБЗОРЫ https://doi.org/10.17816/clinpractXXXX циальной резекции желудка. Авторы указывают на положительное влияние сохранения желудочно-пищеводного сфинктера и кардии желудка для снижения риска развития рефлюкс-синдрома.…”
Section: How To Decide Surgical Procedures Fro Esophagogastric Junctiounclassified